2022
DOI: 10.1177/19418744211067908
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of the Safety of Rapid Administration of Undiluted High-Dose Intravenous Levetiracetam

Abstract: Background Intravenous (IV) levetiracetam (LEV) is an antiseizure medication traditionally given as an intermittent infusion to mitigate potential adverse effects given its acidic formulation. The process of compounding may lead to delays in treating status epilepticus, which is why administration of undiluted doses is of interest. Prior studies have shown safety of IV doses from 1000 mg to 4500 mg; however, assessments of adverse side effects outside IV site reactions have not been studied. Methods A retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 6 publications
(23 reference statements)
2
17
0
Order By: Relevance
“…14 The third trial showed a few cases of hypotension and bradycardia that were explained by other patient factors and no infusion-related reactions. 16 The results discussed in this review article support the safe administration of levetiracetam as a rapid intravenous bolus given over 5 min. This method of administration would be beneficial in all areas of the hospital especially in times of nursing shortages.…”
Section: Discussionmentioning
confidence: 56%
See 4 more Smart Citations
“…14 The third trial showed a few cases of hypotension and bradycardia that were explained by other patient factors and no infusion-related reactions. 16 The results discussed in this review article support the safe administration of levetiracetam as a rapid intravenous bolus given over 5 min. This method of administration would be beneficial in all areas of the hospital especially in times of nursing shortages.…”
Section: Discussionmentioning
confidence: 56%
“…The remaining three retrospective studies evaluated the use of undiluted levetiracetam given as a rapid intravenous infusion and are detailed in Tables 1 and 2 13,14,16 . One study looked specifically at doses of less than or equal to 1000 mg 13 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations